The Effect of Implementing Values Honesty on Earnings Enhance with Customer Satisfaction as a Moderation Variable - Masdar, Nisma Ariskha; Alimuddin, Alimuddin; Mediaty, Mediaty (Universitas Muhammadiyah Sorong, 2025)
This research aims to analyze the impact of honesty values on customer satisfaction and revenue growth at Chocolicious Indonesia. This research proves that the value of honesty has a significant impact on customer satisfaction, but does not directly influence the increase in Chocolicious's revenue. Customer satisfaction has proven to be an important mediator in the relationship between the value of honesty and increase revenue. This research uses a mixed-methods approach. The quantitative approach was used with a survey method for data collection to statistically formulate the hypothesized relationship between the value of honesty, customer satisfaction, and the revenue of Chocolicious Indonesia. As many as 180 questionnaires were distributed to Chocolicious customers, and 100 surveys could be used for testing. This research also uses a descriptive qualitative approach to understand the phenomenon and describe the application of honesty values in maximizing revenue at Chocolicious, focusing on data collection regarding individual perspectives on the application of honesty values in Chocolicious's business practices. These findings indicate that the value of honesty has a significant impact on customer satisfaction, but does not directly influence the increase in Chocolicious's revenue. Customer satisfaction has proven to be a mediator in the relationship between the value of honesty and increase revenue. These findings imply that the application of honesty values, such as selling halal products for consumption, no deception in transactions, no usury during sales, applying honesty in promoting products, and instilling sincerity values among employees, creates customer satisfaction that contributes to increased revenue through repeat purchases by various customers.